Kéziratos könyvek olvasói és befogadói a református egyházban a 18. században - Hegyi Ádám Alex ("... Tanácsaid hűség és igazság": Tisztelgő írások Dienes Dénes professzor úr 65. születésnapjára, 2021)
According to literary history research, one of the most significant differences between printed and manuscript texts was, that manuscripts were read by close-knit communities, while printed books were accessible to everybody. The goal of the Enlightenment was to accomplish as great publicity as possible in 18th century Europe. One typical moment of this was when community reading was transferred to the public space instead of family, church, and courtyards: book clubs and public libraries made reading possible for a wide range of social classes. By comparison, in the Kingdom of Hungary, the Reformed Church was much more close-knit. The Calvinists tried to maintain their literacy with manuscripts: they made large numbers of copies of piety works, worship textbooks, and theological textbooks. Not only copies, but also individual, original works were spread in manuscripts, because their publication would have been impossible anyway. In that way, reformed manuscripts entered the grey zone instead of the public. In their study, we introduce that the closedness of the readers of the reformed manuscripts was diverse: a manuscript could have become well-known to a large group. The reverse also existed: a group of hundreds of members was able to conceal widely known manuscripts from others.